Towards formalising installation and reconfiguration tasks of AADL architecture. (1st January 2013) - Benlahrache, Nadira; Belala, Faiza
Software applications are becoming more and more distributed rendering their deployment (which consists essentially of the installation and dynamic reconfiguration activities) crucial and important phase in software development lifecycle. Although, several approaches for software deployment exist in the literature, most of them deal with specific technologies and offer limited models. In this paper, we focus on the formalisation of the most important deployment tasks of software systems using bigraphical reactive systems (BRS). We aim to give a complete semantic framework for AADL specifications, including the installation of software application on execution platform and its dynamic reconfiguration. AADL offers necessary tools to define both software and execution platform characteristics in the same description. For this purpose, our model allows the specification of software architecture configuration by a suitable pair of bigraphs, the first one models software components and their interconnections, and the second one models the execution platform. Thus, software entities installation on hardware ones is achieved by composing the two designed bigraphs. Besides, reconfiguration activity is formalised in terms of BRS reactions rules.